Are South Korean people willing to pay for official development assistance for building renewable power plants in developing countries?. (July 2018) - Kim, Hyo-Jin; Lee, Hye-Jeong; Yoo, Seung-Hoon
Abstract: The South Korean government is considering financially assisting developing countries to construct renewable power plants both to improve their electricity-related welfare and to reduce CO2 emissions globally. More specifically, official development assistance (ODA) is being planned for building 5 MW wind, photovoltaic, and biomass power plants in developing countries every year from 2017 to 2026. This article aims to evaluate South Korean people's willingness to pay (WTP) for carrying out the ODA plan. To this end, a survey of 1000 households was conducted using the contingent valuation (CV) technique. The mean yearly WTP for the ODA plan implementation is calculated to be KRW 3551 (USD 3.03) per household. When the sample value is expanded to the whole country, it amounted to KRW 68.5 billion (USD 58.5 million) per annum, for the next ten years. The South Korean people's total WTP is more than the cost required, given that the yearly cost is estimated to be about USD 35.0 million. Therefore, the ODA plan execution contributes to the South Korean people's utility and can be done with public support. Highlights: Renewable energy-related official development assistance is widely needed. South Korea will build 5 MW renewable power plants in developing countries yearly. South Korean people's willingness to pay (WTP) for performing the plan is assessed. Mean yearly WTP is calculated to be KRW 3551 (USD 3.03) per household. Its national value is worth KRW 68.5 billion (USD 58.5 million) per year.